2019
DOI: 10.29271/jcpsp.2019.11.1096
|View full text |Cite
|
Sign up to set email alerts
|

Myelofibrosis in Patients of Chronic Myeloid Leukemia in Chronic Phase at Presentation

Abstract: Objective: To determine the frequency and grading of myelofibrosis in patients of chronic myeloid leukaemia in chronic phase, and the association of cytopenias/cytosis with the degree of fibrosis. Study Design: Descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, as the grading of MF seems to vary significantly depending on the individual assessment, another, possibly technology-aided and centralized approach to grade fibrosis in the BM would help to reduce the variations seen in different studies ( Gralnick et al, 1971 ; Kvasnicka et al, 2001 ; Buesche et al, 2003 ; Hamid et al, 2019 ). One major limitation of our study is that in our cohort, only a small number of patients in TFR could be included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the grading of MF seems to vary significantly depending on the individual assessment, another, possibly technology-aided and centralized approach to grade fibrosis in the BM would help to reduce the variations seen in different studies ( Gralnick et al, 1971 ; Kvasnicka et al, 2001 ; Buesche et al, 2003 ; Hamid et al, 2019 ). One major limitation of our study is that in our cohort, only a small number of patients in TFR could be included.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of BM fibrosis is often described with MF grades ranging from lower prefibrotic grade 1 to defined MF with grades 2–3 ( Thiele et al, 2005 ; Swerdlow et al, 2017 ). In CML, the proportion of patients with MF varies widely from 30% to 100% of patients ( Gralnick et al, 1971 ; Kvasnicka et al, 2001 ; Buesche et al, 2003 ; Hamid et al, 2019 ). Interestingly, imatinib seems to be able to either slow down or reverse MF ( Beham-Schmid et al, 2002 ; Bueso-Ramos et al, 2004 ; Thiele et al, 2004 ; Buesche et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among other specific chronic toxicities related to the drug, late occurrence of moderate/severe anemia during long-lasting treatment with imatinib has been reported in a moderate rate of patients and seems to be more common in elderly [5]. It has been recently shown that bone marrow fibrosis is very common in CML patients at diagnosis (65% have grade 1 and 27% grade 2) [6], and that patients with two or more chromosomal abnormalities in Ph'-negative cells (including those that are related to clonal hematopoiesis or myelodysplasia) showed sometimes worse response to TKIs [7]. Thus, several factors could be responsible for developing anemia during imatinib, but its pathogenesis is not fully understood.…”
Section: Introductionmentioning
confidence: 99%